Flow Analysis of a Trihybrid Nanofluid using Local Linearization Method - Kumar, Chinmay; Srivastav, Abhinava; Jain, Lovely (Discontinuity, Nonlinearity, and Complexity, 2026)
This study examines a free convective flow of a trihybrid nanofluid across a truncated cone in a non-Darcy porous medium. Nanoparticles $Fe_3O_4$, $Zn$, and $Au$ are constituents of this trihybrid nanofluid model and these are present in a base fluid, blood. Solving the flow governing equations with related boundary conditions and analyzing fluid behavior and heat transfer include the application of the local linearization method (LLM) with local non-similarity approach. The effect of variation in nanoparticle volume fractions in trihybrid nanofluid on velocity and temperature profiles, also the generation of entropy and Nusselt number, are illustrated and thoroughly examined. The velocity profile increases with the increase in nanoparticle volume fractions for all the three types of nanoparticles. Additionally, the error analysis demonstrates the effectiveness of the previously described solution process. A potential comparison with the published results in the literature is also provided for certain parameter values. This method makes it easier to comprehend the linearized dynamics of a nonlinear system, which helps with prediction and optimization in a variety of domains, including engineering and medicine.